Parallel money markets : vol. 1 the new markets in London - Einzig, Paul (London ; New York : Macmillan; St. Martin's Press, 1971)
This volume covers money markets of overseas financial centers.
Vol 2 available
Includes bibliographical references and index.
rua 28/03/17
Loans
Keywords: Finance; England - London; New York (State)--New York